Melampaui Tradisi: Teknologi, Musik dan Transformasi Budaya (Tinjauan Buku Music and Technoculture) - Rachmawanti, Ranti (Jurnal Sosioteknologi, 2025)
The book "Music and Technoculture" (2003), a collective work edited by René T. A. Lysloff and Leslie C. Gay Jr., is not only an academic publication, but also a monumental milestone that fundamentally reconfigures our understanding of music within the contemporary cultural landscape. This collection of essays boldly advocates for a crucial paradigm shift, moving away from ethnomusicological views and traditional music studies that tend to regard music solely as an isolated “cultural expression.” Instead, Lysloff and Gay Jr., together with their contributors, propose a new framework: music as an entity embedded within a technocultural context. Overall, this book constructs a progressive narrative: from music as a cultural artifact to music as a social space shaped by technology. It positions technology as an agent that mediates not only sound, but also meaning, identity, and social relationships. In a broader context, Music and Technoculture serves as a bridge between music studies, media studies, and cultural theory. This idea has far-reaching implications for the world of contemporary art and culture. In artistic practice, for example, the concept of technoculture offers new insights into how artists interact with digital mediums to create innovative aesthetic forms. Meanwhile, in the context of popular culture, this book helps us understand how digital music, social media, and streaming platforms shape the ways society listens, creates, and interacts.